2019
DOI: 10.3390/ijms20246128
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Secretion of an Atrial Natriuretic Peptide in Beige-Like 3T3-L1 Adipocytes

Abstract: The browning of white adipose tissue (beige adipocytes) stimulates energy expenditure. Omega-3 fatty acids have been shown to induce thermogenic action in adipocytes via G-protein coupled receptor 120 (GPR120). Atrial natriuretic peptide (ANP) is a peptide hormone that plays the role of maintaining normal blood pressure in kidneys to inhibit Na+ reuptake. Recently, ANP was found to induce adipocyte browning by binding to NPR1, an ANP receptor. However, the expression of ANP in adipocytes has not yet been studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
(57 reference statements)
3
5
0
Order By: Relevance
“…These results indicate that Wnta1 promoted ANP secretion and a positive inotropic effect in atrial mechanical dynamics mainly via the WNT/Ca 2+ pathway. The mechanism involved in Wnta1 activation of PKC in the present study is in line with previous studies A C B [9,13] and consistent with investigations showing that activated PKC was effective in promoting the secretion of ANP [21,22]. Our data also support studies reported upregulation of ANP expression after activation of WNT in myocardial hypertrophic animal models [13,20].…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that Wnta1 promoted ANP secretion and a positive inotropic effect in atrial mechanical dynamics mainly via the WNT/Ca 2+ pathway. The mechanism involved in Wnta1 activation of PKC in the present study is in line with previous studies A C B [9,13] and consistent with investigations showing that activated PKC was effective in promoting the secretion of ANP [21,22]. Our data also support studies reported upregulation of ANP expression after activation of WNT in myocardial hypertrophic animal models [13,20].…”
Section: Discussionsupporting
confidence: 93%
“…Expression and secretion of ANP are primarily accomplished in the heart, but ANP expression has been reported to occur in adipocytes as well 31 . Bae et al 32 investigated the expression of ANP in brown/beige adipocytes induced by docosahexaenoic acid, triiodothyronine, or the peroxisome proliferator‐activated receptors (PPARs) agonist rosiglitazone. Brown adipocyte‐specific genes were found to be upregulated in 3T3‐L1 cells with the increased secretion of ANP, suggesting that 3T3‐L1 cells had undergone browning and differentiated into beige‐like adipocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Expression and secretion of ANP are primarily accomplished in the heart, but ANP expression has been reported to occur in adipocytes as well. 31 Bae et al 32 between cGMP and mTORC1 activation and that mTORC1 activation was necessary for NP-induced browning of adipocytes. They also confirmed that mTORC1 was involved in both PKA and PKG-mediated pathways, which demonstrated its importance in the adipose browning process.…”
Section: The Relationship Between the Anp System And Batmentioning
confidence: 99%
“…23 T3 promotes the expression of PGC-1α, the master transcriptional coactivator of mitochondrial biogenesis in fat depots to enhance BAT thermogenesis. 24 The results of an animal study suggested that thyroid hormone also additionally mediates UCP-1-independent thermogenesis. 25 BAinduction treatment did not increase the expression of UCP-1 in adipocytes derived from the obese group, but mitochondrial respiratory function, PGC-1α gene expression did increase significantly, which may due to the effect of T3, although the content of increasement was lower compared to normal-weight ones.…”
Section: Discussionmentioning
confidence: 99%